A comunicação suplementar e alternativa na construção da linguagem de crianças com paralisia cerebral: análise de uma proposta de intervenção - Carvalheira, Germana Maria Gomes (2007)
This study had the main purpose to identify the benefits of using the alternative communication as an assistant resource for language construction in children with cerebral palsy. The specific goals were to describe the most used communicative means by the child investigated; identify the communicative profile communicative functions, used by the child in situations of interaction with the mother, in order to follow the progress in using an Alternative System of Communication (ASC); and analyzing if happened any variation in the relation between the linguistic competence and the level of interaction after the therapeutic intervention. For that, it was adopted a qualitative, quantitative and longitudinal approach, of the type Study of Case. Participated, from this study, one mother-child dyad. The child has the neurological diagnosis of Cerebral Palsy, with a clinical frame of spastic diplegia with the left dimidium more damaged (MSE) motor level III. The constitution of the corpus had three stages: initially, it was made a collect of informations about the child (anamnesis) and a speech evaluation, through two meetings with the dyad. Afterward, it was recorded the first video during the dyad s free interaction And, in the last stage of collect, it was made a second and last video recorder of a dyad s free interaction, after four months of speech therapy intervention. The results reveal that the child used, in the interaction with the mother, largely, interactive functions grouped as: those used to control or regulate the other s behavior and the background (asks of: information, object, action, assent, social routine and protest); for the social interaction (comment, protest expression, performative and narrative) and those used to establish the shared attention (exhibition, shared game and other s recognizing). The most used communicative means was the gestual/vocal, displaying an increase in the gestuality, so the child, further than pointing more and using gestures, the child also used the folder of communication. The results indicate that the child s communication had the functions of control and interaction. These data show that the child uses the communication with the aim of social interaction. These data point, also, to difficulties in the attention mediation with the other, that may be a child s difficulty because of the pathology, suggesting variations in the professional approach about assistance to the family, for example, introducing an alternative System of Communication (ASC)